Design of A Low-Voltage Distribution Panel Based on Recycled Plastic Material for Corrosive Environments - Frangky Delano Winston Palendeng; Christy Natalie Tampi; Ketly Oktavia Miranda Lasut; Donald Bastian Noya; Marson James Budiman (Journal of Social Research, 2026)
The increasing deployment of low-voltage distribution panels in coastal and industrial environments has created significant challenges due to corrosion, material degradation, and maintenance requirements of conventional metallic enclosures. Corrosion exposure can reduce equipment reliability, increase operational costs, and compromise electrical safety. This study aimed to design and evaluate a low-voltage distribution panel using recycled high-density polyethylene (rHDPE) as an alternative enclosure material for corrosive environments. The research employed an experimental approach involving material preparation, panel design, mechanical and electrical characterization, corrosion resistance testing, and verification based on IEC 61439-1 standards. The rHDPE compound was developed from post-consumer HDPE with magnesium hydroxide reinforcement and evaluated through tensile strength, impact resistance, dielectric strength, volume resistivity, salt spray exposure, and panel-level electrical performance tests. The results showed that the rHDPE panel achieved adequate mechanical properties with 93% retention of tensile strength and impact resistance compared with virgin HDPE, while providing superior electrical insulation performance with a dielectric strength of 18 kV/mm. The corrosion test demonstrated complete resistance after 500 hours of salt spray exposure, with no mass loss, surface degradation, or electrical resistance changes, whereas the mild steel reference panel experienced significant corrosion deterioration. IEC 61439-1 verification confirmed that the proposed panel met safety and performance requirements. The study concludes that recycled HDPE is a feasible, sustainable, and cost-effective material for low-voltage distribution panels, offering corrosion immunity, reduced maintenance, and environmental benefits.